Menanamkan Nilai-Nilai Sopan Santun Pada Anak-Anak Dengan Kegiatan Bermain Dan Edukasi Di Desa Janji Matogu Pardomuan Kecamtan Angkola Selatan Kabupaten Tapanuli Selatan - Dani, Suci Rahma (EL-EMIR INSTITUTE, 2025)
This study aims to describe the strategy and implementation of play and educational activities as effective media in instilling good manners in children in Janji Matogu Pardomuan Village, South Angkola District, South Tapanuli Regency. The method used is a descriptive qualitative approach through observation, interviews, and documentation of teachers, parents, and children at Janji Matogu Elementary School. The results show that play activities combined with educational approaches, such as role-playing, drama, and social activities in the village environment can improve children's polite behavior in daily interactions. Children become more accustomed to saying hello, asking permission, thanking, and showing respect to others. Supporting factors for the success of this activity include teacher involvement, the active role of parents, and the support of the village community who uphold the local cultural values ​​of the Angkola Batak. The conclusion of this study confirms that play and educational activities contextualized with local culture are an effective and enjoyable method for instilling good manners in children in rural areas.